Integrated Mobile Management System (IMMS) - Cepillo, Jeannette B. (2002)
The Integrated Mobile Management System (IMMS) is an application of the Wireless Application Protocol technology. This technology was created together with the growing demand on getting information with just one click on wireless devices, such as cellular phones. The IMMS is a project that implements an Integrated Information Center. Using the Linux-Mandrake Platform and Web Applications, users who have access to this application can have their phonebook and inbox memory extended through the use of the MySQL Database. The database will store SMS contact information of people that the user adds in the phonebook. The user can send text messages to all or selected people in the database, as well as retrieve text messages that are stored in the database. The stored messages can be forwarded to one or more contact numbers that are specified by the user. Moreover, the application gives the users the chance to benefit additional services such as specifying events in a calendar of activities, and informing them about these events, through SMS.